PELATIHAN KETERAMPILAN KEWIRAUSAHAAN: PENGENALAN IDE BISNIS UNTUK MEMPERKUAT FONDASI BISNIS BAGI MAHASISWA PROGRAM STUDI ILMU POLITIK, FISIP UNIVERSITAS HALU OLEO TAHUN 2024 - Arief, Iriyani Astuti; Syahadat, Muh. Ishak; Efrianto, La Ode; Lestari, Indra (Universitas Halu Oleo, 2024)
Entrepreneurship Skills Training: Introduction Business Ideas to Strengthen Business Foundations for Students of the Political Science Study Program, FISIP Halu Oleo University, aims to increase students understanding of determining business ideas in order to reduce intellectual unemployment and create jobs. Because of this, the service team will provide business concepts to the participants as part of an entrepreneurial skills training programme. This was done considering that students still have low awareness of determining business ideas and becoming entrepreneurs, so that they are able to change their mindset from job seekers to job makers. The service team will impart knowledge and invite young entrepreneurs to share their experiences in coming up with business concepts through this training method. The Political Science Study Programme at FISIP UHO was one of the partners with which the service team worked on this project. The results of this service can be seen from the students understanding in determining business ideas, from students who initially did not how to determine a business idea, They are excited to start a business that will help them further their skills as beginner business owners now that they know this. The service team invited speakers who are current Browniesta Kendari owners, to provide students with knowledge on how to identify business ideas so that they are able to become crative and innovative young entrepreneurs.